Policy Shocks and Market-Based Regulations: Evidence from the Renewable Fuel Standard. (14th February 2018) - Lade, Gabriel E; Lin Lawell, C -Y Cynthia; Smith, Aaron
Abstract: The Renewable Fuel Standard mandates large increases in U.S. biofuel consumption and is implemented using tradable compliance credits known as RINs. In early 2013, RIN prices soared, causing the regulator to propose reducing future mandates. We estimate empirically the effect of three "policy shocks" that reduced the expected mandates in 2013. We find that the largest of these shocks decreased the value of the fuel industry's 2013 compliance obligation by 7 billion. We then study the effects of the shocks on commodity markets and the market value of publicly-traded biofuel firms. Results show that the burden of the mandate reductions fell primarily on advanced biofuel firms and commodity markets of the marginal compliance biofuel. We argue that the policy shocks reduced the incentive to invest in the technologies required to meet the future objectives of the RFS, and discuss alternative policy designs to address the problems that arose in 2013.